14X-(6X-8)=1

Simple and best practice solution for 14X-(6X-8)=1 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 14X-(6X-8)=1 equation:


Simplifying
14X + -1(6X + -8) = 1

Reorder the terms:
14X + -1(-8 + 6X) = 1
14X + (-8 * -1 + 6X * -1) = 1
14X + (8 + -6X) = 1

Reorder the terms:
8 + 14X + -6X = 1

Combine like terms: 14X + -6X = 8X
8 + 8X = 1

Solving
8 + 8X = 1

Solving for variable 'X'.

Move all terms containing X to the left, all other terms to the right.

Add '-8' to each side of the equation.
8 + -8 + 8X = 1 + -8

Combine like terms: 8 + -8 = 0
0 + 8X = 1 + -8
8X = 1 + -8

Combine like terms: 1 + -8 = -7
8X = -7

Divide each side by '8'.
X = -0.875

Simplifying
X = -0.875

See similar equations:

| .08x+28.3=.5x-9.5 | | -4.64+(-3.4)=0 | | D=58t | | in(x)+in(3X)=12 | | 40x+(8*1.5x)=640 | | -6=2(w-8)-7w | | 4(5x+2)=40 | | 15x-(5x-4)=24 | | 40x+(8(1.5x))=640 | | 5(x+y)=3x+2y | | -15.4-3.5t=-(9.5t+0.4) | | -(6x-5y+4)= | | 5.1p-0.7(2+3p)=-10.4 | | 3/4y-6=1/4y+10 | | 28--4d=5d-17 | | 4+2(x-3)=20 | | 6x+6+2(9x-4)= | | 2b-3-10b-9= | | i(-i)= | | 0.25(8+4x)-0.5(10+2x)= | | 9w+w+8w= | | 3(x-1)+2(4x-5)=(x-3)+5 | | -2(7z+5)=-14z+13 | | 2sin^2x+3sinx+1=0 | | 3n^2-9n-3=0 | | -6w+19=8w+5 | | y+0.6y-1.2=2(y-1.4) | | -12x-14=-2(6x+7) | | h=-1+3l^2+s | | In(x-5)+In(x+6)=1 | | m^2+2mn-3n^2=0 | | X-3y=600 |

Equations solver categories